The relationships between organizational cynicism, high performance work system, perceived psychological contract violation, workplace incivility and organizational citizenship behaviour among secondary school teachers in Johor Bahru, Malaysia - Baig, Javaria (2019)
Despite the decades of empirical researches on organizational citizenship behaviour, still many of its aspects are unexplored. Organizational citizenship behaviour is found to be important in education sector, especially in public schools in Malaysia. Hence, this study has been conducted to investigate the relationships of organizational citizenship behaviour with high performance work system, perceived psychological contract violation and workplace incivility with organizational cynicism as intervening variable. The research framework has been formulated using the expectancy theory. This is a quantitative study. Stratified random sampling was used to distribute the survey questionnaires to a total of 341 public secondary school teachers in Johor Bahru, Malaysia. The data was analysed by SPSS and SmartPLS 3. The results from Structure Equation Modeling (SEM) revealed that organisational cynicism fully mediates the relationship between high performance work system and organisational citizenship behaviour, it partially mediates the relationship between perceived psychological contract violation and organisational citizenship behaviour and it partially mediates the relationship between workplace incivility and organizational citizenship behaviour. This study finds that teachers’ attitude and behaviour are affected by extra responsibilities with least incentives, unmet expectations, lack of involvement in decision making and mistreatment at workplace all of which reduce their organisational citizenship behaviour. This study recommends to provide human resource training programs which enhance teachers’ career, citizenship behaviour and communication skills with their co-workers. The management should also have an adequate feedback system, clear job description and work performance-based incentives in schools to reduce behavioural issues among public school teachers. This would bring extensive benefits to schools and teachers as well.